MORPHOLOGICAL CHARACTERS STUDY FOR ELEVEN SPECIES BELONGS TO BRASSICACEAE FAMILY IN IRAQ - Marwa. K. Mathree; S. A. Aliwy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was amied to investigate morphological characteristics of pollen grains and fruits for eleven species belonging to the tribe Brassiceae of cruciferae family, species are: Brassica rapa L , Braasica deflexa Boiss. ,Brassica nigra (L.) brassica juncea(L.), Brassica tournefortii Gouan, Brassica oleracea L., sinapis arvensis L., Hirschfeldia incana(L.) ,Savignya paraflora(Del.) ,Raphanus sativus L. ,Eurca sativa Mill., pollen grains were studied morphologically and all dimentions were recorded. The result of this study showed that most pollen grains are tricolpate ,their size varied between small ,medium and ornamentation was reticulated. The morphological study of fruits showed a contrast in the ornamentation between reticulate, smooth reticulate and rough reticulate ,it’s also varied in color, shape and dimensions.